Applying the genetic theories of ageing to the cytoplasm: cytoplasmic genetic covariation for fitness and lifespan. - Dowling, D.K.; Maklakov, A.A.; Friberg, U.; Hailer, F. (Journal of Evolutionary Biology, 2009)
Two genetic models exist to explain the evolution of ageing - mutation accumulation (MA) and antagonistic pleiotropy (AP). Under MA, a reduced intensity of selection with age results in accumulation of late-acting deleterious mutations. Under AP, late-acting deleterious mutations accumulate because they confer beneficial effects early in life. Recent studies suggest that the mitochondrial genome is a major player in ageing. It therefore seems plausible that the MA and AP models will be relevant to genomes within the cytoplasm. This possibility has not been considered previously. We explore whether patterns of covariation between fitness and ageing across 25 cytoplasmic lines, sampled from a population of Drosophila melanogaster, are consistent with the genetic associations predicted under MA or AP. We find negative covariation for fitness and the rate of ageing, and positive covariation for fitness and lifespan. Notably, the direction of these associations is opposite to that typically predicted under AP.